2014
DOI: 10.1007/s11136-014-0713-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural and psychometric validation of the Dispositional Resilience Scale (DRS-15) in Chinese adult women

Abstract: The C-DRS-15 was demonstrated to be a reliable and valid measurement to assess hardiness in Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
3
28
0
2
Order By: Relevance
“…The validity and reliability of the DRS-15 have been demonstrated in studies conducted in various countries (Hystad et al, 2010;Picardi et al, 2012;Solano et al, 2016;Wong et al, 2014). The results of the present study provide support for the validity and reliability of the KDRS-15 in measuring hardiness in Korean adults.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The validity and reliability of the DRS-15 have been demonstrated in studies conducted in various countries (Hystad et al, 2010;Picardi et al, 2012;Solano et al, 2016;Wong et al, 2014). The results of the present study provide support for the validity and reliability of the KDRS-15 in measuring hardiness in Korean adults.…”
Section: Discussionsupporting
confidence: 78%
“…The criterion validity of the DRS-15 was assessed using the 20-item KCES-D to measure depression, which has been shown to be closely associated with resilience in previous studies (Dowrick, Kokanovic, Hegarty, Griffiths, & Gunn, 2008;Gito, Ihara, & Ogata, 2013;Jeste et al, 2013). In addition, depression was chosen to assess known-group validity, as previous studies have reported that depressed individuals were less resilient relative to non-depressed individuals (Davydov, Stewart, Ritchie, & Chaudieu, 2010;Southwick, Vythilingam, & Charney, 2005;Wong et al, 2014). Responses are provided using a 4-point Likert scale, and total scores range from 0 to 60.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the DRS-15 has undergone multiple revisions with the hopes of addressing issues of inconsistent measurement, it is still common to have variations in factor structure between the three subcomponents and one overarching construct based on the sample using the measures (e.g., Kardum, Hudek-Knezevic, & Krapic, 2012;Wong et al, 2014). Thus, in the current study, the factor structure of the DRS-15 will be assessed with the study sample prior to completing additional statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Per the widely accepted theory of hardiness, the 3 C's should be highly correlated and secondary to the overarching hardiness factor (e.g., Maddi, 2002;Orr & Westman, 1990;Ouellette, 1993), however, variations in this factor structure have been seen in more recent studies (e.g., Kardum et al, 2012;Wong et al, 2014), which has led some researchers to call for the domains to be studied separately (Sinclair & Tetrick, 2000).…”
Section: Factor Structure Of the Drs-15mentioning
confidence: 99%